PERALIHAN HAK TANGUNGAN SECARA DIBAWAH TANGAN ATAS TANAH AGUNAN PT. BANK RAKYAT INDONESIA CABANGSINTONG KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR RIAU - Dewo, Punto; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
As you can see, the community has made lending and borrowing activities something that is very much needed to support the development of their economic activities and to improve their standard of living. Lenders who have excess money or excess funds are willing to provide loans to those who need it. On the other hand, the borrower is based on a specific need or purpose to borrow the money.The problem that the writer makes the basis of this research is how the implementation of the transfer of mortgage rights at PT. Bank Rakyat Indonesia branch of Duri Desa Sintong Pusaka, Tanah Putih Subdistrict, What are the factors that caused the transfer of underhand mortgage rights at PT. Bank Rakyat Indonesia, branch of Duri Desa Sintong Pusaka, Tanah Putih Subdistrict and, What are the legal consequences arising from the Underhand Transfer of Mortgage Rights.This type of research can be classified into the type of empirical or sociological research, because in this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at PT. Bank Rakyat Indonesia, data sources used are: primary data and secondary data, data collection techniques in this study with observation, interviews and literature review.The results of this study are first. The implementation of the transfer of security rights must be carried out in accordance with Law Number 4 of 1996 concerning Mortgage Rights that the transfer can be carried out if the creditor knows and the transfer must be registered at the land office and must have a deed of transfer of mortgage rights, the two factors causing the transfer of Mortgage Rights are below hands are: Economic factors, Unable to make repayments, Ignorance of applicable rules, The amount of costs to be incurred, Looking for more profit. And thirdly, the legal consequences arising from the transfer of mortgage rights under the hand according to Article 11 paragraph 1 of the Mortgage Rights Law states that the transfer must include the names and identities of the parties and their domicile, while the transfer under the hands does not state this so the legal consequences arise. is null and void because the provisions of the article are compelling.Keywords: Mortgage, Debtor, Creditors